Cost Volume Profit Analysis in Procurement of New Machinery as a Basis for Margin Contribution at PT. X in Jakarta - Rizqi, Muhamad Nur; Hurriyaturrohman, Hurriyaturrohman; Mulyana Dali, Rahmat (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2024)
The purpose of this study is to determine the profit and loss budget of the Printing company